Ischaemic stroke as the first presentation of antineutrophilic cytoplasmic autoantibody‐associated vasculitis. Issue 12 (9th December 2022) - Tran, John Chuan Nguyen; Abasszade, Joshua Haron; Dang, Yew Li; Crompton, Douglas Ewan
Abstract: The diagnosis of antineutrophil cytoplasmic autoantibody‐associated vasculitis in first‐episode strokes is particularly challenging, especially in patients lacking features of systemic vasculitis. We present the case of a 71‐year‐old woman with positive myeloperoxidase antineutrophil cytoplasmic antibodies and negative proteinase 3 autoantibodies. The patient presented with 1 week history of pyramidal weakness in both upper and lower limbs, hyperreflexia, and clonus. Magnetic resonance imaging of the brain demonstrated widespread bihemispheric cortical and deep white matter acute infarcts, which are consistent with features of stroke secondary to vasculitis. Myeloperoxidase antineutrophilic cytoplasmic autoantibody‐positive vasculitis diseases are more commonly associated with renal, pulmonary, and cutaneous manifestations; however, in our patient, the central nervous system features predominated. This case highlights the challenges of diagnosing primary central nervous system vasculitis, in this case, an atypical myeloperoxidase antineutrophilic cytoplasmic autoantibody‐positive disease without the classical disease course and clinical signs. Abstract : The diagnosis of antineutrophil cytoplasmic autoantibody‐associated vasculitis (AAV) in first‐episode strokes is challenging, especially in patients lacking features of systemic vasculitis. Central nervous system involvement may be the only manifestation of AAV and, consequently, should be considered as a cause of stroke especially in multifocal infarcts.